The Effectiveness Of Chewing Apples On The Plaque Index In Primary School Children (Literature Study) - Nadira, Rahma; Sari, Multia Ranum; Sari, Ernita (International Journal of Health Sciences, 2024)
Chewing apples is an alternative for reducing the plaque index on teeth, because apples contain vitamins and tannins which function to clean teeth and freshen the mouth to avoid gum disease caused by plaque on teeth. The aim of this study was to determine the effectiveness of chewing apples on reducing the plaque index on the teeth of elementary school children. The type of research used is literature study. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. The results of previous studies that have been reviewed from several journals or other references show the effectiveness before and after chewing apples on the plaque index on teeth. The release of saliva and assisted by the water content in apples is able to clean food residue stuck to the surface of the teeth. The conclusion is that chewing any type of apple can provide better effectiveness in reducing the plaque index on teeth. Chewing apples can be used as a natural ingredient to reduce the plaque index on teeth.